Diversity of Mosquitoes in Jalna urban, Maharashtra State, India - J.C. Bhandari, E. L. Jaid*, S. V. Nikam, B.V. More and (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Present paper deals with the study of diversity of mosquitoes in Jalna urban of Maharashtra state in one year that is from June 2008 to May 2009. During a period of two years a total number of 1998 mosquitoes were collected and examined. Percentage density of different genera was found as Anopheles-64.71%; Aedes-19.61%; Culex-11.61% and Mansonia-4.05%.